Grafted glass microspheres and preparation method and application thereof
By introducing highly reactive polyether groups to the surface of hollow glass microspheres, grafted glass microspheres are prepared, which solves the problem of the reduction in elastic recovery rate of the sealant under temperature difference, windy or earthquake conditions, and achieves the high elastic recovery rate and good construction properties of the sealant.
Patent Information
- Application Number
- CN202310521851.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-10
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-05-10
AI Technical Summary
The existing sealant frequently expands and shrinks in the event of temperature changes, windy or earthquakes, resulting in a decrease in elastic recovery rate and is unable to continuously perform waterproofing functions.
Grafted glass microspheres are used to modify the surface of hollow glass microspheres and introduce high-reactive polyether groups to improve the elastic recovery rate of the sealant.
The elastic recovery rate of modified silicone building sealant is achieved by more than 85%, while improving the constructionability of sealant.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sealants, and in particular to a grafted glass microsphere and a preparation method thereof and application in the field of sealants. Background Art
[0002] Modified silicone building sealant, also known as MS sealant, is a new type of sealing material. It was first developed by Kaneka Corporation of Japan in the 1970s. It is a silane-modified polymer prepared by mixing polyether as the main raw material, supplemented by fillers, catalysts, coupling agents, dewatering agents, etc. MS sealant combines the advantages of silicone sealant and polyurethane sealant, and has good weather resistance, non-toxic and harmless. It is an environmentally friendly new sealant suitable for the field of prefabricated buildings. At present, prefabricated buildings require MS sealants to have lower modulus, higher elastic recovery rate, good deformation resistance, thixotropy and effective anti-aging.
[0003] In the case of large temperature difference, strong wind or frequent earthquakes, the sealing materials between building boards are often in a state of continuous expansion and contraction. Therefore, the MS sealant must not break or peel off, and can continue to play a waterproofing function, and must have good elongation and resilience. CN108102593A discloses a low modulus and high resilience prefabricated concrete building modified silane sealant and its preparation method. Diisodecyl phthalate is used as a plasticizer. The product has good extrudability, and the elongation and resilience are maximized.
[0004] However, the maximum rebound rate (i.e. elastic recovery rate) disclosed in the above patent application is 72%. Hollow glass microspheres can be used as a semi-reinforcing filler in MS sealants. Due to their micron-sized particle size and rigidity, although they can shorten the surface drying time and reduce the thermal conductivity, they will cause the elongation and elastic recovery rate of the MS sealant to drop seriously, and the elastic recovery rate is only 30% to 45%. Summary of the invention
[0005] In view of this, an object of the present invention is to provide a grafted glass microsphere and a preparation method thereof, so that a highly active polyether group is grafted on the surface of a hollow glass microsphere, thereby making the elastic recovery rate of the prepared modified silicone building sealant reach more than 85%.
[0006] The second object of the present invention is to provide a MS sealant and a preparation method thereof, wherein the sealant adopts the grafted glass microspheres and cooperates with other raw materials in the sealant to improve the elastic recovery rate of the sealant while improving its workability.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A grafted glass microsphere comprises a hollow glass microsphere, an alkoxy group and a highly active polyether segment formed on the surface of the hollow glass microsphere, and a trace amount of isocyanate group is also contained on the surface of the hollow glass microsphere.
[0009] The grafted glass microspheres are mainly prepared by reacting the following raw materials in parts by weight: 20 to 30 parts of glass microspheres, 3 to 8 parts of a first silane coupling agent, and 3 to 8 parts of a highly active polyether diol.
[0010] Among them, when the hydroxyl value of the polyether diol is relatively low, its viscosity is usually relatively large, the reaction activity is relatively small, and the hydroxyl content is relatively small at the same grafting rate. The grafted glass microspheres obtained in this way are difficult to improve the elongation at break and elastic recovery rate of the MS glue colloid.
[0011] When the hydroxyl value of the polyether diol is relatively high, its viscosity is usually relatively small, the reaction activity is relatively high, the grafting rate is high, and the hydroxyl content is relatively high. The grafted glass microspheres obtained in this way have a relatively high degree of crosslinking with the MS resin, which makes the MS glue colloid strength and hardness relatively high, and the elongation at break and elastic recovery rate relatively low.
[0012] Therefore, the hydroxyl value of the highly active polyether diol is 30-110, the viscosity is 150-750 mPa·s, and the molecular weight is 1000-3500, such as DL-3000D, Arcol Polyol 1011, etc. In this way, the polyether group on the grafted glass microspheres obtained has a relatively good bonding strength with both the glass microspheres and the MS resin, so that the MS colloid can have a good elongation at break and elastic recovery rate.
[0013] Preferably, the hollow glass microspheres have a true density of 0.37 to 0.62 g / cm 3 , at least one of which has a particle size in the range of 25 to 40 μm. The first silane coupling agent is 3-isocyanate propyl trimethoxy silane, 3-isocyanate propyl triethoxy silane or any mixture thereof.
[0014] The raw materials of the grafted glass microspheres further include: 150-200 parts by mass of an organic solvent and 0.05-0.1 parts by mass of a first catalyst.
[0015] Preferably, the organic solvent is a mixture of one or more of ethanol, isopropanol, dimethyl carbonate, ethyl acetate and butyl acetate.
[0016] The first catalyst is an organic acid tin salt such as dibutyltin dilaurate, dibutyltin dichloride, stannous octoate or dimethyltin diceneodecanoate.
[0017] A method for preparing grafted glass microspheres comprises: firstly modifying glass microspheres with a first silane coupling agent to obtain coupling agent modified glass microspheres; and then reacting the coupling agent modified glass microspheres with highly active polyether diols to obtain the grafted glass microspheres.
[0018] Based on the above, the step of obtaining the coupling agent modified glass microspheres includes: heating the coupling agent solution and the first catalyst under stirring and reflux to obtain the coupling agent mixed solution; then spraying the coupling agent mixed solution onto the surface of the hollow glass microspheres, and under stirring, reacting the first silane coupling agent with the hydroxyl groups on the surface of the hollow glass microspheres at 50°C to 80°C to form alkoxy groups and isocyanate groups on the surface of the hollow glass microspheres to obtain the coupling agent modified glass microspheres and obtain the coupling agent modified glass microsphere solution; wherein the coupling agent solution is a mixture of the first silane coupling agent and an organic solvent.
[0019] Specifically, the first silane coupling agent and the organic solvent are uniformly mixed to obtain a coupling agent premix; the coupling agent premix and the first catalyst are then heated and refluxed under stirring to obtain the coupling agent mixed solution; the coupling agent mixed solution is then sprayed onto the surface of the hollow glass microspheres, and reacted at 50°C to 80°C under stirring to obtain the coupling agent modified glass microsphere solution. The coupling agent mixed solution is prepared by stirring and heating under reflux, which can not only fully mix the raw materials therein, but also preheat to remove small molecules therein.
[0020] More specifically, the organic solvent and the first silane coupling agent are dispersed with a magnetic stirrer for 10 to 15 minutes to prepare the coupling agent premix; the catalyst and the coupling agent premix are then heated and refluxed at 150 to 200 r / min for 5 to 10 minutes to prepare the coupling agent mixed solution, which is then sealed and stored; the hollow glass microspheres are placed in a rotating mixer with a speed set to 5 to 10 r / min and a temperature set to 50° C. to 80° C., and the coupling agent mixed solution is sprayed onto the hollow glass microspheres within 60 minutes, and the reaction is continued for 3 to 5 hours after spraying to prepare the coupling agent modified glass microsphere solution.
[0021] Based on the above, the step of preparing the grafted glass microspheres includes: stirring the coupling agent modified glass microsphere solution and the highly active polyether diol at 70°C to 75°C to allow the isocyanate groups on the surfaces of the coupling agent modified glass microspheres to completely react with the highly active polyether diol, so that the alkoxy groups and highly active polyether segments are formed on the surfaces of the glass microspheres.
[0022] Specifically, the coupling agent modified glass microsphere solution and the highly active polyether diol are placed in a stirring kettle, reacted for 1.5 to 2.5 hours at a rotation speed of 100 to 250 r / min and a temperature of 70° C. to 75° C., cooled to room temperature, filtered and dried at 55° C. to 60° C. to prepare the grafted glass microspheres.
[0023] The invention discloses an application of grafted glass microspheres in preparing MS sealant.
[0024] The MS sealant comprises the following raw materials in parts by weight: 80-120 parts of MS resin, 60-90 parts of plasticizer, 3-6 parts of dewatering agent, 100-150 parts of nano-activated calcium carbonate, 20-40 parts of the above-mentioned grafted glass microspheres, 0.5-1 part of anti-yellowing agent, 3-6 parts of second silane coupling agent, and 0.5-1.5 parts of second catalyst.
[0025] The MS resin has a viscosity of no more than 30,000 cps at 25°C.
[0026] The plasticizer is selected from at least one of diisodecyl phthalate, dioctyl phthalate, diphenyl isodecyl phosphate and alkylphenyl sulfonate.
[0027] The dehydrating agent is a vinyl functional silane dehydrating agent, and more preferably at least one of vinyl trimethoxy silane, vinyl triethoxy silane and vinyl methyl dimethoxy silane.
[0028] The anti-yellowing agent is selected from one or more of BETTERSOL1513, BETTERSOL1830, UV770, UV328 and UV245.
[0029] The second silane coupling agent is selected from one or more of r-glycidyloxypropyltrimethoxysilane, r-glycidyloxypropyltriethoxysilane, r-aminopropyltrimethoxysilane and r-aminopropyltriethoxysilane.
[0030] The second catalyst is chelated tin, dibutyltin dilaurate, dibutyltin dichloride or bismuth neodecanoate.
[0031] A method for preparing MS sealant comprises: in a vacuum state, firstly mixing MS resin, plasticizer and dehydrating agent, then adding dehydrated nano-active calcium carbonate to mix, then adding dehydrated grafted glass microspheres to mix, then adding a second silane coupling agent and an anti-yellowing agent to stir, and finally adding a second catalyst to react.
[0032] The preparation method specifically comprises: firstly, dehydrating calcium carbonate and grafted glass microspheres at 100°C to 110°C for 3 to 6 hours, placing MS resin, plasticizer and dehydrating agent in a double planetary stirring kettle, mixing for 5 to 8 minutes at a vacuum degree of less than -0.08 MPa and 20 to 30 r / min, then adding calcium carbonate, stirring for 30 to 50 minutes at a vacuum degree of less than -0.095 MPa and 40 to 50 r / min, then adding glass microspheres, stirring for 10 to 15 minutes at a vacuum degree of less than -0.095 MPa and 20 to 25 r / min, then adding a second silane coupling agent and an anti-yellowing agent, stirring for 10 to 15 minutes at a vacuum degree of less than -0.095 MPa and 20 to 25 r / min, and finally adding a catalyst, stirring for 10 to 15 minutes at a vacuum degree of less than -0.095 MPa and 20 to 25 r / min after the addition, and removing from the kettle.
[0033] Compared with the prior art, the technical solution provided by the present invention has the following advantages:
[0034] First, the grafted glass microspheres provided by the present invention are first modified by a first silane coupling agent on the surface of the glass microspheres, and then a highly active polyether is grafted onto the surface thereof, so that the surface of the glass microspheres contains highly active polyether segments, alkoxy groups and trace isocyanate groups, thereby improving the surface polarity of the glass microspheres. The hydroxyl groups in the highly active polyether segments on the surface of the grafted glass microspheres can undergo a cross-linking reaction with the MS resin, thereby converting the glass microspheres from "hard segments" into softer segments, which can well maintain the elongation at break and elastic recovery rate of the modified silicone building sealant, especially achieving an elastic recovery rate ≥ 85%.
[0035] Second, since the grafted glass microspheres provided by the present invention have both a large number of highly active polyether segments and a trace amount of isocyanate groups on their surfaces, applying them to the MS sealant is equivalent to adding an adhesion promoter, which is beneficial to improving the adhesion of the MS sealant. Therefore, the MS sealant provided by the present invention not only has excellent physical and mechanical properties, but can also achieve 100% cohesive destruction of the cement substrate without primer, thereby simplifying the construction process.
[0036] Third, due to the spherical shape of the glass microspheres and the low oil absorption value, the viscosity of the MS sealant provided by the present invention is relatively low, the extrusion volume is greatly increased, and the construction is convenient. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is further described in detail below through specific implementation methods. Among them, the glass microsphere raw materials used in the following embodiments or comparative examples are all products of our company.
[0038] Examples 1-3 Grafted glass microspheres
[0039] Examples 1 to 3 provide a grafted glass microsphere, including a hollow glass microsphere and an alkoxy group, a highly active polyether segment and a trace amount of isocyanate group formed on the surface of the hollow glass microsphere. The grafted glass microsphere is mainly prepared from the raw materials shown in Table 1.
[0040] Table 1 Grafted glass microsphere raw material mass ratio table
[0041]
[0042] The preparation method of the grafted glass microspheres provided in Examples 1 to 3 comprises: dispersing ethyl acetate and 3-isocyanatepropyltrimethoxysilane using a magnetic stirrer for 10 min to prepare the coupling agent premix; then heating dibutyltin dilaurate and the coupling agent premix at 180 r / min for 5 min to prepare the coupling agent mixed solution, and sealing and storing; preparing a 0.38 g / cm 3 The glass microspheres are placed in a rotating mixer with a speed set to 5 r / min and a temperature set to 80°C. The coupling agent mixed solution is sprayed onto the hollow glass microspheres within 60 min, and the reaction is continued for 4 h after spraying to prepare the surface-treated glass microsphere solution. The surface-treated glass microsphere solution and DL-3000D are reacted in a stirring kettle at a speed of 200 r / min and a temperature of 70°C for 2.5 h, and then cooled to room temperature. After filtration, the glass microspheres are taken out and dried at 60°C to prepare the grafted glass microspheres.
[0043] Examples 4-6 MS building sealant
[0044] Examples 4 to 6 each provide a MS building sealant, which is prepared from the raw materials shown in Table 2.
[0045] Table 2 MS building sealant raw material mass ratio
[0046]
[0047] The preparation method of MS building sealant provided in Examples 4 to 6 comprises: firstly, dehydrating nano-active calcium carbonate and the grafted glass microspheres shown in Table 2 at 110° C. for 4 h, placing Asahi Glass 888E, diisodecyl phthalate and vinyl trimethoxysilane in a double planetary stirring kettle, mixing for 6 min at a vacuum degree of less than -0.08 MPa and 25 r / min, then adding the dehydrated nano-active calcium carbonate, stirring for 50 min at a vacuum degree of less than -0.095 MPa and 40 r / min, then adding the dehydrated grafted glass microspheres, stirring for 10 min at a vacuum degree of less than -0.095 MPa and 25 r / min, then adding r-aminopropyl trimethoxysilane and BETTERSOL1513, stirring for 10 min at a vacuum degree of less than -0.095 MPa and 25 r / min, and finally adding chelated tin KRA-1, and stirring for 10 min at a vacuum degree of less than -0.095 MPa and 25 r / min after the addition. min, get out of the cauldron.
[0048] Example 7
[0049] The present embodiment provides a grafted glass microsphere, comprising a hollow glass microsphere and a highly active polyether segment, an alkoxy group and a trace amount of isocyanate group formed on the surface of the hollow glass microsphere. The grafted glass microsphere is mainly prepared from the raw materials shown in Table 3.
[0050] Table 3 The mass proportion of raw materials for grafted glass microspheres provided in this example
[0051] Glass Microspheres <![CDATA[True density 0.62 g / cm 3 > 20 The first silane coupling agent 3-Isocyanatepropyltriethoxysilane 5 Organic solvents Dimethyl carbonate 150 Highly active polyether diol Arcol Polyol 1011 hydroxyl value 110, viscosity 150 cp, molecular weight 1000 5 First Catalyst SLD101 Jilin Huaxin 0.06
[0052] The present embodiment provides a method for preparing the above-mentioned grafted glass microspheres, comprising: dispersing dimethyl carbonate and 3-isocyanate propyltriethoxysilane using a magnetic stirrer for 15 minutes to prepare the coupling agent premix; then heating the catalyst SLD101 Jilin Huaxin and the coupling agent premix at 150 r / min for reflux for 10 minutes to prepare the coupling agent mixed solution, and sealing and storing; placing the hollow glass microspheres in a rotating mixer with a speed set to 10 r / min and a temperature set to 50°C, spraying the coupling agent mixed solution onto the hollow glass microspheres within 60 minutes, and continuing to react for 3 hours after spraying, so as to prepare the surface-treated glass microsphere solution; the surface-treated glass microsphere solution and ArcolPolyol 1011 are set in a stirring kettle with a speed of 200 r / min and a temperature of 75°C for 1.5 hours, and then cooled to room temperature. After filtration, the glass microspheres are taken out and dried at 55°C to prepare the grafted glass microspheres.
[0053] Example 8
[0054] This embodiment also provides a MS building sealant, which is prepared from the raw materials shown in Table 4.
[0055] Table 4. Ratio of raw materials of MS building sealant provided in this embodiment.
[0056]
[0057] The present embodiment provides a preparation method of the provided MS building sealant, comprising: firstly, dehydrating nano-activated calcium carbonate and grafted glass microspheres at 105° C. for 3 h, placing Kalkonium 203H, Kalkonium 303H, diisodecyl phthalate and vinyl trimethoxysilane in a double planetary stirring kettle, mixing for 8 min at a vacuum degree of less than -0.08 MPa and 20 r / min, then adding the dehydrated nano-activated calcium carbonate, stirring for 30 min at a vacuum degree of less than -0.095 MPa and 50 r / min, then adding the dehydrated grafted glass microspheres, stirring for 15 min at a vacuum degree of less than -0.095 MPa and 20 r / min, then adding r-glycidyl ether oxypropyl trimethoxysilane and BETTERSOL1830, stirring for 15 min at a vacuum degree of less than -0.095 MPa and 20 r / min, finally adding chelated tin, and stirring at a vacuum degree of less than -0.095 MPa and 20 r / min after the addition. Stir at rpm for 15 min and remove from the kettle.
[0058] Comparative Examples 1 to 6
[0059] Comparative Examples 1 to 4 each provide a MS building sealant, whose raw material composition and preparation method are basically the same as those of corresponding Examples 4 to 6 and 8, with the main difference being that Comparative Examples 1 to 4 use original glass microspheres that have not been grafted to replace the grafted glass microspheres provided in corresponding Examples 1 to 4 and Example 7.
[0060] Comparative Example 5 provides a MS building sealant, whose raw material composition and preparation method are basically the same as those of the corresponding Example 6, with the main difference being that an equal volume of heavy calcium carbonate is used in this Comparative Example 5 to replace the grafted glass microspheres provided in Example 3.
[0061] Comparative Example 6 provides a MS building sealant, whose raw material composition and preparation method are basically the same as those of Example 4, with the main difference being that: this Comparative Example 6 uses active polyether DL-400 instead of DL-3000D used in Example 1.
[0062] Performance verification test
[0063] The following tests were conducted on the density, elastic recovery rate, tensile strength, extrusion amount, and bonding form performance of the MS building sealants provided in Examples 4 to 6, Example 8, and Comparative Examples 1 to 6. The test results are shown in Table 5.
[0064] 1) Density: Place the sample and density cup under standard test conditions for more than 4 hours, clean and dry the density cup with volume v with alcohol, and determine its mass as m0. Fill the density cup with the sample, remove the bubbles in the sample in a vacuum dryer, close the lid tightly, keep the overflow port open, wipe off the overflow with alcohol, and determine its mass as m1, with an accuracy of 0.001g. Density ρ is calculated as follows:
[0065] ρ = (m1-m0) / v
[0066] Where: ρ is the sample density, g / cm 3 ;
[0067] m0 is the mass of the empty weight cup, g;
[0068] m1 is the mass of the weight cup filled with the sample, g;
[0069] v is the density cup capacity, 37 or 50, cm 3 or ml.
[0070] 2) Elastic recovery rate: The elastic recovery rate of the cement substrate was tested in accordance with GB / T13477.17-2017 8.2A when using a primer (Kaneka EX-104) or primer-free.
[0071] 3) Tensile strength under standard conditions: The tensile strength of the cement substrate was tested in accordance with GB / T13477.8-2017 when using a primer or primer-free. The test sample was cured under standard conditions for 28 days, and the tensile strength was measured and the damage was recorded.
[0072] 4) Extrusion volume: tested according to GB / T13477.3-2017, extrusion aperture 4 mm, air pressure 300 kPa.
[0073] Table 5 MS building sealant performance test results
[0074]
[0075] Combined with Table 5, compared with Comparative Examples 1 to 4, the density of the MS building sealants provided by Examples 4 to 6 and 8 of the present invention is equivalent, the tensile strength does not change much, but the elastic recovery rate and extrusion amount are significantly improved, and the bonding formation is basically 100% cohesive failure.
[0076] Compared with Comparative Example 5, the density of the MS building sealant provided in Example 6 is lower, and the tensile strength does not change much, but the elastic recovery rate, extrusion amount and bonding form are obviously better.
[0077] The density and tensile strength of the MS building sealant provided by Comparative Example 6 and Example 4 are equivalent. The extrusion amount of Example 4 is slightly higher, but the elastic recovery rate and bonding form are significantly better than those of Comparative Example 6. It can be seen that the selection of active polyether is more important. When the hydroxyl value of the highly active polyether diol is 30-60110, the viscosity is 150-750 mPa·s, and the molecular weight is 1000-3500, the prepared MS building sealant will have a better elastic recovery rate and 100% cohesive failure.
[0078] From the perspective of tensile strength, elastic recovery rate and bonding failure form, the data of the MS building sealant provided by the embodiment of the present invention are equivalent with or without a primer for cement substrate; while the data of the control example with or without a primer are quite different, or the elastic recovery rate is relatively low. Therefore, the MS building sealant provided by the embodiment of the present invention can be primer-free, and the tensile strength, elastic recovery rate and bonding failure form are also relatively good.
[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A grafted glass microsphere, characterized in that: It comprises hollow glass microspheres and alkoxy and highly active polyether segments formed on the surface of the hollow glass microspheres; The invention is mainly prepared by the following method: firstly modifying hollow glass microspheres with a first silane coupling agent under stirring to obtain coupling agent modified glass microspheres; then reacting the coupling agent modified glass microspheres with high-activity polyether diols to obtain the grafted glass microspheres; wherein, by weight, the first silane coupling agent is 3 to 8 parts, the hollow glass microspheres are 20 to 30 parts, and the high-activity polyether diol is 3 to 8 parts; the high-activity polyether diol has a hydroxyl value of 30 to 110, a viscosity of 150 to 750 cps, and a molecular weight of 1000 to 3500; the first silane coupling agent is 3-isocyanate propyl trimethoxy silane, 3-isocyanate propyl triethoxy silane, or any mixture of the two; and the high-activity polyether diol is DL-3000D or Arcol Polyol 1011.
2. The grafted glass microsphere according to claim 1, characterized in that: The raw materials also include: 150-200 parts by weight of an organic solvent and 0.05-0.1 parts by weight of a first catalyst.
3. A method for preparing the grafted glass microspheres according to claim 1, comprising: Under stirring, firstly modifying the hollow glass microspheres with a first silane coupling agent to obtain coupling agent-modified glass microspheres; The coupling agent-modified glass microspheres are then reacted with highly active polyether diols to obtain the grafted glass microspheres; wherein, by weight, the first silane coupling agent is 3 to 8 parts, the hollow glass microspheres are 20 to 30 parts, and the highly active polyether diol is 3 to 8 parts.
4. The preparation method according to claim 3, characterized in that: The step of obtaining the coupling agent modified glass microspheres comprises: heating the coupling agent solution and the first catalyst under stirring and reflux to obtain the coupling agent mixed solution; then spraying the coupling agent mixed solution onto the surface of the hollow glass microspheres, and under stirring, reacting the first silane coupling agent with the hydroxyl groups on the surface of the hollow glass microspheres at 50° C. to 80° C. to form alkoxy groups and isocyanate groups on the surface of the hollow glass microspheres to obtain the coupling agent modified glass microspheres and obtain the coupling agent modified glass microsphere solution; wherein the coupling agent solution is a mixture of the first silane coupling agent and an organic solvent, the organic solvent is 150 to 200 parts by mass, and the first catalyst is 0.05 to 0.1 parts by mass.
5. The preparation method according to claim 4, characterized in that: The step of preparing the grafted glass microspheres comprises: stirring the coupling agent modified glass microsphere solution and the highly active polyether diol at 70° C. to 75° C. to allow the isocyanate groups on the surfaces of the coupling agent modified glass microspheres to completely react with the highly active polyether diol, so that the alkoxy groups and highly active polyether segments are formed on the surfaces of the glass microspheres.
6. The preparation method according to claim 4, characterized in that: The step of preparing the grafted glass microspheres comprises: placing the coupling agent modified glass microsphere solution and the highly active polyether diol in a stirring kettle, reacting for 1.5 to 2.5 hours at a rotation speed of 100 to 250 r / min and a temperature of 70° C. to 75° C., cooling to room temperature, filtering and drying at 55° C. to 60° C. to prepare the grafted glass microspheres.
7. Use of the grafted glass microspheres according to any one of claims 1 to 2 in the preparation of modified silicone building sealants.
8. The use according to claim 7, characterized in that: The modified silicone building sealant comprises the following raw materials in parts by weight: 80-120 parts of MS resin, 60-90 parts of plasticizer, 3-6 parts of dewatering agent, 100-150 parts of nano-activated calcium carbonate, 20-40 parts of grafted glass microspheres according to any one of claims 1 to 2, 0.5-1 part of anti-yellowing agent, 3-6 parts of second silane coupling agent, and 0.5-1.5 parts of second catalyst.
9. A method for preparing MS sealant, comprising: Under vacuum, firstly mix the MS resin, plasticizer and dehydrating agent, then add the dehydrated nano-active calcium carbonate and mix, then add the dehydrated grafted glass microspheres according to any one of claims 1 to 2 and mix, then add the second silane coupling agent and anti-yellowing agent and stir, and finally add the second catalyst to react.
Citation Information
Patent Citations
Modified silane sealant with low modulus and high resiliency for prefabricated concrete buildings and preparation method of modified silane sealant
CN108102593A
Low-modulus high-adhesion assembling type silane modified polyether adhesive used for building, and preparation method thereof
CN108179000A